Nearly parallel helical vortex filaments in the three-dimensional Euler equations - Guerra-Benavente, I (SPRINGER HEIDELBERG, 2026)
Klein, Majda, and Damodaran have previously developed a formalized asymptotic motion law describing the evolution of nearly parallel vortex filaments within the framework of the three-dimensional Euler equations for incompressible fluids. In this study, we rigorously justify this model for two configurations: the central configuration consisting of regular polygons of N helical-filaments rotating with constant speed, and the central configurations of N+1\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$N+1$$\end{document} vortex filaments, where an N-polygonal central configuration surrounds a central straight filament.